Variation in the number of copies and in the genomic organization of ecotropic murine leukemia virus proviral sequences in sublines of AKR mice. - Buckler, C E (1982)
DNAs isolated from individual mice of four AKR sublines (AKR/J, AKR/N, AKR/Cum, and AKR/Boy) were examined by hybridization of electrophoretically separated restriction enzyme fragments to a 500-base pair, 32P-labeled probe specific for env sequences of ecotropic murine leukemia virus. Variation in the number of proviral DNA copies and in their genomic organization, as reflected by the location of restriction enzyme sites in flanking cellular sequences, was observed both between and within AKR sublines. Evidence is presented for the continual acquisition of new proviruses in the four sublines studied. The ecotropic proviral DNA copies present in the four AKR sublines can be related to their genealogy; each subline contains two or three copies of proviral DNA in common with other sublines and from one to six unique ecotropic proviruses. Overall, a new copy appears about every 12 generations of inbreeding. Some of the unique proviral DNA copies contain internal alterations, as reflected by restriction enzyme maps that differ from those of prototype ecotropic proviruses.